Attitude of would-be medical graduates toward rural health services: An assessment from Government Medical Colleges in Chhattisgarh - Meeta Jain; Shubhra Agrawal Gupta; Anil Kumar Gupta; Pritam Roy (Journal of Family Medicine and Primary Care, 2016)
Background: Understanding the attitude toward rural health care among future medical graduates, the health workforce of the near future, is an important exercise. Objective: The objective of this study is to understand the attitude of third year MBBS students in a Government Medical College of Chhattisgarh toward rural health services. Methodology: A cross-sectional study was conducted in 2014 using a semi-open-ended questionnaire. The analysis was primarily descriptive, and nonparametric test of significance was used. Results: Of a total of 293 students, 263 (89.7%) rated the current rural health services to be unsatisfactory. Nearly 44% students were willing to serve in the rural area. There was no statistical difference among willing and nonwilling 3rd year Part I students regarding willingness to join rural services but mostly not willing among 3rd year Part II. Majority (66.2%) were only willing to work in rural areas for <1 year. The oft-mentioned reason was reservation or added marks in postgraduate entrance examination by more than two-third respondents, “health services for the poor” by nearly two-third respondents and followed by “gain of knowledge about rural people and their diseases.” Nearly 10% would-be medical graduates perceived no apparent benefit. The greatest perceived disadvantage was “lack of infrastructural facilities” by more than 80% of the respondents, while “lack of education opportunities for children and basic amenities for family members” was a concern for nearly three-fourth of respondents. Less than half of the respondents thought that there were no career growth opportunities in rural practice. Conclusion: If the identified perceived factors of nonwillingness are taken care off, it would lead to a drastic increase in the number of doctors joining rural service. Not only that but also this would lead to more doctors staying in their position for a longer duration than currently mandated. This would require a relook at the preexisting health policies and adapting them accordingly to retain the services of rural health workers.